Epistemological beliefs, metacognitive awareness, self- efficacy and goal orientations as predictors of knowledge acquisition among pre-service teachers in Northern Nigeria - Jikamshi, Mahmud Haruna (2016)
The aim of this study is on the relationships between epistemological beliefs, metacognitive awareness, self-efficacy, goal orientations, knowledge acquisition approaches among pre-service teachers in Northern Nigeria. Data was collected through the use of five different self-reported instruments and the entire instruments used were adopted and permission was thought from the original authors. There are a total of 418 participants who are pre-service teachers, consisting of 215 males and 203 females. Multi-stage Cluster sampling technique was used to collect data and Path analysis was employed as a statistical technique for the data analysis. The analyses revealed that, majority of pre-service teachers are inclining to surface knowledge acquisition approach when compared to those who employed deep knowledge acquisition approach. And a greater number of them have naïve epistemological belies, low metacognitive awareness, low self-efficacy, low learning goal orientation and higher in performance goal orientation. Specifically, this inquiry examined the relationships between epistemological beliefs, metacognitive awareness, self-efficacy, goal orientation and knowledge acquisition approaches among pre-service teachers in Nigeria and the findings revealed significant relationships between epistemological beliefs, metacognitive awareness, self-efficacy, goal orientation (exogenous variables) and knowledge acquisition approaches (endogenous variables). The study also revealed that epistemological beliefs, metacognitive awareness, learning goal orientation significantly predict surface knowledge acquisition approachHowever, self-efficacy and performance goal orientation did not predict surface knowledge acquisition approach. Also The finding of this study revealed that learning goal orientation mediate the relationships between epistemological beliefs, metacognitive awareness, self-efficacy, and both deep and surface knowledge acquisition approaches among pre-service teachersin Nigeria. However, performance goal did not mediate with epistemological beliefs and self-efficacy. This suggests that learning goal orientation is good mediator in this relationship. This study has a significant theoretical and practical implication for educators and college lectures in understanding these relationships. And practically, thus help the educators or college lectures to select the best learning strategy for their students.